2022
DOI: 10.1177/03635465211073341
|View full text |Cite
|
Sign up to set email alerts
|

Association of Radiographic Markers of Hip Instability and Worse Outcomes 2 to 4 Years After Hip Arthroscopy for Femoroacetabular Impingement in Female Patients

Abstract: Background: Reported outcomes of patients undergoing hip arthroscopy for femoroacetabular impingement (FAI) with underlying borderline acetabular dysplasia are mixed. This may in part be the result of mixed-sex reporting. Purpose: To determine the effect of radiographic measures of acetabular dysplasia and hip instability on outcomes of female patients undergoing hip arthroscopy for FAI. Study Design: Case-control study; Level of evidence, 3. Methods: This was a retrospective study of female patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Developmental dysplasia of the hip is a complex tridimensional pathology, and defining it by solely the LCEA is oversimplistic 26,54,58,59 . The anterior wall index, posterior wall index, and femoroepiphyseal acetabular roof index are radiographic markers of hip instability that were not included in this investigation 60 . Recently, the inside-out pattern of chondral damage on the acetabulum 61 , in addition to other intraoperative findings of hip instability during hip arthroscopy, was described 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Developmental dysplasia of the hip is a complex tridimensional pathology, and defining it by solely the LCEA is oversimplistic 26,54,58,59 . The anterior wall index, posterior wall index, and femoroepiphyseal acetabular roof index are radiographic markers of hip instability that were not included in this investigation 60 . Recently, the inside-out pattern of chondral damage on the acetabulum 61 , in addition to other intraoperative findings of hip instability during hip arthroscopy, was described 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Though good clinical effects were achieved after surgery [8,9]. Many demographic factors can influence the clinical outcomes of hip arthroscopy, such as higher age, higher BMI, and female patients [10][11][12][13][14], of which obesity demonstrated a twofold increased risk of conversion to total hip arthroplasty [15].…”
Section: Introductionmentioning
confidence: 99%
“… 19 Hip dysplasia has been associated with microinstability and poor outcomes when treated with hip arthroscopy alone. 27 , 29 Periacetabular osteotomy (PAO) has demonstrated reliability and durability in treating patients with hip dysplasia at short-, mid-, and long-term follow-ups. 4 , 5 , 17 A 2019 study by Ziran et al 39 reported favorable outcomes even 20 years after surgery.…”
mentioning
confidence: 99%